An air-stable n-type bay-and-headland substituted bis-cyano N–H functionalized perylene diimide for printed electronics. Issue 39 (30th September 2021) - Park, Irene E.; Brixi, Samantha; Martell, Mark; Ocheje, Michael U.; Pettipas, Richard D.; Harris, Dylan H.; Gelfand, Benjamin S.; Rondeau-Gagné, Simon; Lessard, Benoit H.; Welch, Gregory C.
Abstract : Design, synthesis, and characterization of an electron deficient N-H functionalized perylene diimide, with halogen-free solvent solubility, for air-stable transistor operation. Abstract : The synthesis of a 6, 11-bis-cyano N–H functionalized perylene diimide is reported. Electron withdrawing cyano groups were installed to counter the electron donating cyclic amine moiety with retention of functionality. Solution-processed, air-stable organic field-effect transistors are demonstrated using this new material.